PEMBERDAYAAN KEMAMPUAN BERWIRAUSAHA KELOMPOK PENGANGGURAN PERKOTAAN - Ibnu Syamsi (Jurnal Kependidikan, 2008)
The purpose of this study was to make a device of the development of an entrepreneurship training, develop a model of theentrepreneurship training, and create the material ofentrepreneurship training for the employment of joblesstownspeople. The study employed research and development as themethod and used qualitative and quantitative approaches as themethods of analyses. After a series of try-outswere conducted, thereal field operational test was performed by using a pre-test andpost-test design. The data were collected through interviews,participative observations, intensive discussion, documentationstudy, and questionnaires. A mark-test was utilized for thedescriptiveand inferential statistical calculations. Findings of thestudy consisted of a design of the entrepreneurship training devicefor the applicant of the fresh entrepreneur group in the city, a modelof entrepreneurship training for the employment of joblesstownspeople, an entrepreneurship training material modulefor theemployment of joblesstownspeople, and an effective model ofentrepreneurship training and material for the employment ofjobless townspeople.